ACHALASIA OF THE CARDIA - Mohammad, Gul; Ghani, Rehman; Nabi, Ghulam (Journal of Ayub Medical College Abbottabad, 1992)
ABSTRACT: Achalasia of the cardia is an uncommon neuromuscular disorder originally described by Willis in 1972. Ernst Hellar performed the 1st successful cardiomyotomy for this condition on 14th April, 1913 by performing only anterior myotomy. Zaaijer modification of Heller’s procedure is most often performed today. The result of cardiomyotomy are generally satisfactory but patient might have persistent or recurrent difficulty in swallowing or develop new symptoms of reflex oesophagitis and stricture. We have case reports of two cases where this operation was performed without any of these complication so far.